Restrukturisasi Syariah: Upaya Penyelesaian Cidera Janji (Wanprestasi) Investasi Syariah - Budi Santoso, M. Syafi’i; Nur Husen, Muhammad; Ilma Ahmad, Zakiyyah; Dimyati, Dimyati (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
Default in this sharia investment practice is when the issuer is unable to pay the obligations that should be paid to the securities holders (investors) according to the agreed terms when the maturity date has arrived. This study will examine in depth related to the efforts to settle defaults (default) on Sharia Investments with Sharia Restructuring. The method used in this research is to use a qualitative approach that is library research using books or journals. recognized restructuring in accordance with the basic principles of sharia: First, the restructuring of sukuk is carried out by creating the same economic results as conventional bonds by maintaining sharia principles so that all sukuk transactions must be halal. Second, the form of avoiding restructuring requires the prohibition of usury (paying or taking interest), gharar (unclear, fraud, ambiguity) and maysir (embedding games). Sukuk certificate holders can only receive benefits from asset performance and are prohibited from making payments under any circumstances in a sukuk restructuring. Third, the prohibition of investments that are not based on sharia principles. Keywords: Default, Sharia Investment, Restructuring